Genetically determined cutaneous nevi and risk of cancer. Issue 6 (20th November 2021) - Dusingize, Jean Claude; Law, Matthew H.; Pandeya, Nirmala; Neale, Rachel E.; Ong, Jue‐Sheng; MacGregor, Stuart; Whiteman, David C.; Olsen, Catherine M.
Abstract: Numerous epidemiologic studies have reported positive associations between higher nevus counts and internal cancers. Whether this association represents a true relationship or is due to bias or confounding by factors associated with both nevus counts and cancer remains unclear. We used germline genetic variants for nevus count to test whether this phenotypic trait is a risk‐marker for cancer. We calculated polygenic risk scores (PRS) for nevus counts using individual‐level data in the UK Biobank (n = 394 306) and QSkin cohort (n = 17 427). The association between the nevus PRS and each cancer site was assessed using logistic regression adjusted for the effects of age, sex and the first five principal components. In both cohorts, those in the highest nevus PRS quartile had higher risks of melanoma than those in the lowest quartile (UK Biobank odds ratio [OR] 1.42, 95% confidence interval [CI]: 1.29‐1.55; QSkin OR 1.58, 95% CI: 1.29‐1.94). We also observed increases in risk of basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) associated with higher nevus PRS quartiles (BCC UK Biobank OR 1.38, 95% CI: 1.33‐1.44; QSkin OR 1.20, 95% CI: 1.05‐1.38 and SCC UK Biobank OR 1.41, 95% CI: 1.28‐1.55; QSkin OR 1.44, 95% CI: 1.19‐1.77). We found no consistent evidence that nevus count PRS were associated with risks of developing internal cancers. We infer that associations between nevus counts and internal cancers reported in earlier observational studies arose because of unmeasured confounding or other biases. Abstract : What's new? Melanocytic nevi, while benign, are known phenotypic risk factors for melanoma. Evidence increasingly suggests that they also raise the risk for internal cancers, including breast and thyroid cancers. Here, the authors examined potential links between nevus count and internal cancer risk using polygenic risk scores based on germline genetic variants for nevus count. The authors' assessments show that while genetically determined nevus count is associated with risk of melanoma, genetic risk for nevi has little association with internal cancer. The data indicate that nevi do not have a causal role in the development of internal cancers.